A Reflection on the Theoretical and Practical Aspects of the Cooperation of Third States with the International Criminal Court - Farveh Farhadi babadi; Sadeq Salimi; Soudeh Shamlou (پژوهشهای حقوقی, 2023)
The idea of establishing an International Criminal Court can be considered as a transformational and developmental idea in the field of international law. Following the Nuremberg trials, the drafting and adoption of the Rome Statute is considered an important document in the realm of international criminal law. This document, unlike the founding documents of the Ad Hoc tribunals, is an international treaty. Therefore, it is subject to the provisions of customary international law governing international treaties. This statute is a development and codifying treaty. In addition, not all state are parties to this treaty and therefore some states are considered third parties to it. In the present article, the concept of a third state in the framework of the Rome Statute has been studied descriptively-analytically. The question then arises as to whether the principle of relativity of treaties applicable to the Rome Statute also is subject to exceptions. According to the findings of this study, the Rome Statute is subject to some exceptions, such as: the existence of a customary rule, the existence of a jus cogense rule, the decision of the Security Council and the consent of the concerned state to the application of the treaty. It is important to note, however, that the extension of the Court's jurisdiction to a state not party to the Statute, outside of what is provided for in the Statute, cannot be consistent with the spirit of criminal law as set forth in the Statute.